Computational methods for pigmented skin lesion classification in images: review and future trends - Oliveira, Roberta B.; Papa, Joao P. [UNESP]; Pereira, Aledir S. [UNESP]; Tavares, Joao Manuel R. S. (Springer, 2018)
Skin cancer is considered as one of the most common types of cancer in several countries, and its incidence rate has increased in recent years. Melanoma cases have caused an increasing number of deaths worldwide, since this type of skin cancer is the most aggressive compared to other types. Computational methods have been developed to assist dermatologists in early diagnosis of skin cancer. An overview of the main and current computational methods that have been proposed for pattern analysis and pigmented skin lesion classification is addressed in this review. In addition, a discussion about the application of such methods, as well as future trends, is also provided. Several methods for feature extraction from both macroscopic and dermoscopic images and models for feature selection are introduced and discussed. Furthermore, classification algorithms and evaluation procedures are described, and performance results for lesion classification and pattern analysis are given.
Keywords: Pattern analysis; Feature extraction and selection; Classification methods; Macroscopic and dermoscopic images